Answer:
![\displaystyle x_1 = 2-√(3) \text{ and } y_1 = (√(3)-1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/college/8m25ulhuivivno3904bwumur3nq7gz293a.png)
Or:
![\displaystyle x _ 2 = 2 + √(3) \text{ and } y _ 2 = -(1+√(3))/(2)](https://img.qammunity.org/2022/formulas/mathematics/college/jlquom78p02e6nvvgpj9l2jwat5jopbc4p.png)
Explanation:
We are given the equation:
![\displaystyle (x^2 + 2xy) + i(y-1) = (x^2 -2x + 2y) - i(x +y)](https://img.qammunity.org/2022/formulas/mathematics/college/brwqobd8brqzaueb1xxtv2hh5xre1pjkfk.png)
And we want to find the values of x and y such that the equation is true.
First, distribute:
![\displaystyle (x^2 + 2xy) + i(y-1) = (x^2 -2x + 2y) +i(-x -y)](https://img.qammunity.org/2022/formulas/mathematics/college/jx755qx2wls8e48ijg0y87txh16a39p04p.png)
If two complex numbers are equivalent, their real and imaginary parts are equivalent. Hence:
![\displaystyle x^2 + 2xy = x^2 - 2x +2y \text{ and } y - 1 = -x -y](https://img.qammunity.org/2022/formulas/mathematics/college/ezicnxe4m86axo93f76bvmnis7bojq88lx.png)
Simplify:
![\displaystyle 2xy = -2x +2y \text{ and }x = 1 - 2y](https://img.qammunity.org/2022/formulas/mathematics/college/wxigm047q5p11dlowu6gpzyicv4mpchkov.png)
Substitute:
![\displaystyle 2(1-2y)y = -2(1-2y) + 2y](https://img.qammunity.org/2022/formulas/mathematics/college/sxl3jkkttszvj6y4v6rtrhjqaijnb3x341.png)
Solve for y:
![\displaystyle \begin{aligned} 2(y - 2y^2) &= (-2 + 4y) + 2y \\ 2y - 4y^2 &= 6y -2\\ 4y^2 + 4y - 2& = 0 \\ 2y^2 + 2y - 1 &= 0 \\ \end{aligned}](https://img.qammunity.org/2022/formulas/mathematics/college/xp9ukhb9gpiqqxgsji9dn5uorfv5tq7p1k.png)
From the quadratic formula:
![\displaystyle \begin{aligned} y &= (-(2)\pm√((2)^2 - 4(2)(-1)))/(2(2)) \\ \\ &= (-2\pm√(12))/(4) \\ \\ &= (-2\pm2√(3))/(4)\\ \\ &= (-1\pm√(3))/(2) \end{aligned}](https://img.qammunity.org/2022/formulas/mathematics/college/jlx83brta0hjmqfuhjxu8bloh40n7aq0tg.png)
Hence:
![\displaystyle y_1 = (-1+√(3))/(2) \text{ or } y_2 = (-1-√(3))/(2)](https://img.qammunity.org/2022/formulas/mathematics/college/a2mxhr62epbreqofyolee2vu7zefpkg6py.png)
Then:
![\displaystyle x _ 1 = 1 - 2\left((-1+√(3))/(2)\right) = 1 + (1 - √(3)) = 2 - √(3)](https://img.qammunity.org/2022/formulas/mathematics/college/cnbty3iksw6dvkndztpxfwafi35hsjkye2.png)
And:
![\displaystyle x _ 2 = 1 - 2\left((-1-√(3))/(2)\right) = 1 + (1 + √(3)) = 2 + √(3)](https://img.qammunity.org/2022/formulas/mathematics/college/1z1tsrjkz39jej766gy093dju90gowmdny.png)
In conclusion, the values of x and y are:
![\displaystyle x_1 = 2-√(3) \text{ and } y_1 = (√(3)-1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/college/8m25ulhuivivno3904bwumur3nq7gz293a.png)
Or:
![\displaystyle x _ 2 = 2 + √(3) \text{ and } y _ 2 = -(1+√(3))/(2)](https://img.qammunity.org/2022/formulas/mathematics/college/jlquom78p02e6nvvgpj9l2jwat5jopbc4p.png)